1987
DOI: 10.1111/j.1365-2125.1987.tb03119.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the response of the renin‐angiotensin system in determining blood pressure changes with sodium restriction.

Abstract: There is controversy about the efficacy of sodium restriction in the treatment of hypertension. Short‐term restriction of sodium intake in normotensive subjects causes little or no fall in blood pressure. This lack of response of blood pressure to sodium restriction appears to be due, at least in part, to a reactive rise in renin and angiotensin II. In patients with essential hypertension there is suppression of the renin‐angiotensin system particularly as blood pressure becomes more severe. With sodium restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Correlation of urinary excretion of NOX on the diet with a low sodium level with the SSI was not significant (ρ 0.255, p 0.12, n 39). The changes in urinary excretion of NOX were not significantly different in the two groups (low-SSI group, 251 [ 16,414] µmol/day, and high-SSI group, 25 [ 213, 297] µmol/day, p 0.14). The changes in plasma NOX were not different (low-SSI group, 0.8 [ 3.6, 22.3] µmol/l, and high-SSI .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Correlation of urinary excretion of NOX on the diet with a low sodium level with the SSI was not significant (ρ 0.255, p 0.12, n 39). The changes in urinary excretion of NOX were not significantly different in the two groups (low-SSI group, 251 [ 16,414] µmol/day, and high-SSI group, 25 [ 213, 297] µmol/day, p 0.14). The changes in plasma NOX were not different (low-SSI group, 0.8 [ 3.6, 22.3] µmol/l, and high-SSI .…”
Section: Resultsmentioning
confidence: 86%
“…Reactive increases in PRA and ALD during sodium restriction are important for the maintenance of blood pressure in normotensive subjects (16,17). However, in hypertensive patients, especially sodium-sensitive ones, the reactive increases in PRA and ALD are attenuated and the blood pressure is lowered when sodium intake is restricted (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of ACE inhibitors revived the argument as to the usefulness of PRA as a marker for their relative effectiveness (Case et al, 1977); much of the clinical work on this has been done by MacGregor and is described elsewhere in this volume (MacGregor, 1987 (Grassi etal., 1985). This, however, does not necessarily help in selecting those patients whose increased sympathetic activity differentiates them from other groups of hypertensive patients, and which might form the basis for drug selection.…”
Section: Smentioning
confidence: 99%
“…3 The mechanisms for these differences in BP response to salt reduction are not fully understood. It has been suggested that the responsiveness of the reninangiotensin system (RAS) plays an important role, 6 but the sympathetic nervous system, 7,8 the kallikrein-kinin system, 9 the nitric oxide system, 10 and many eicosanoids 11 may also contribute. However, the evidence for many of these is circumstantial, whereas the evidence for the important role of the RAS is substantial and compelling.…”
Section: Introductionmentioning
confidence: 99%